Ṣūrat Al-Adab Al-Tarbawiy Al-Insāniy Fi Al-Makhṭūṭat: Murāja’at ‘Ilmiyyat Li A’māl Al-‘Alim Al-Indunisiy - Iin Suryaningsih (Review of Islam in Southeast Asia, 2018)
This research is based on the lack of humanistic pedagogy study which was born from the literary works of Nusantara written in manuscript by applying perfectly the Arab metrum in it. The presence of various modern pedagogical currents carried by the sociologists and observers of Western education, has made a new mapping in the study of modern education in the archipelago. Indeed the study has been popular since the early 20th century AD with a very specific theme evidenced by one of the manuscripts entitled Mir'ātu Afkār al-Rijāl Nadzm Ta'līm al-Muta'līm by a scholar from Solo. This study will prove the perfect application of the themes of Islamic pedagogy and Arabic metrum in the archipelago which is very concerned about the humanist value of the learner by displaying the harmony of the word-for-word pattern written in it. The method used is descriptive method of analysis which includes textual criticism in manuscript, that is so that text can be read well and photographing applying of humanist pegagogy and Arabic metrum. The result of this research is that the humanist flows of pedagogy in the archipelago adopt the Islamic pedagogy and Arabic sciences are perfectly proven with specific themes and patterns of rhythm / rhythm formation in the poetry text.